Effect of Variety and Maturity Index on the Physicochemical Parameters Related to Virgin Olive Oil from Wudu (China) - Fengxia Tang; Chuan Li; Xiaoran Yang; Jiandu Lei; Hongxia Chen; Changwei Zhang; Chengzhang Wang (Foods, 2022)
Physical parameters (i.e., extraction yield, oil content), chemicals (i.e., fatty acids, phenolics) and oxidative stability associated with virgin olive oil (VOO) from ten varieties in Wudu, China, were analyzed as a function of maturity index and variety by multivariate analysis models. Most of the analytical parameters were significantly affected by the variety and maturity index, and the former was more influential than the latter. Phenolics were the principal factor dividing the ten varieties into four groups. High phenolic levels were observed in the ‘Koroneiki’ group and ‘Manzanilla’ group, but the oil extractability index differentiated between them, being the highest and lowest, respectively. The ‘Koroneiki’ group demonstrated high oil productivity and oil quality, which was worthy of promotion in large-scale cultivation. High amounts of linoleic enhanced the VOO health benefits of ‘Ascolana tenera, Arbequina and Zhongshan24’ group, but brought the risk of shortening the shelf-life. The ‘Ulliri Bardhe, Empeltre, Ezhi8, Yuntai14 and Picual’ group clustered for the higher relative value of oleic acid. The maturity index had significant negative effects on the content of total phenolics, oleacein, oleocanthal, and oleic acid, but had a positive effect on the extractability index, which suggested that varieties with low phenolics and oleic acid levels should be harvested early.